DEVELOPMENT OF A WEB-BASED ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT SYSTEM FOR IMPROVING CUSTOMER SERVICE IN RETAIL BUSINESSES - Puspita Rini; Masitah Handayani; Sudarmin (Jurnal Sistem Informasi, 2026)
The development of information technology encourages businesses to adopt digital systems to improve customer service and operational efficiency. Small retail businesses often face challenges in managing customer data and transactions due to manual processes, which can lead to inefficiencies and data inconsistencies. This study aims to design and implement a web-based Electronic Customer Relationship Management (E-CRM) system to support customer data management and enhance service quality. The research method used is the Software Development Life Cycle (SDLC) with the Waterfall model, which includes requirement analysis, system design, implementation, testing, and evaluation. Data were collected through observation, interviews, and documentation. The system was tested using Black Box Testing to ensure that all functionalities operate as expected. The results show that the developed system is able to integrate customer data, transaction records, order monitoring, and customer feedback into a unified platform, thereby improving service efficiency and reducing data recording errors. The implementation of the system also enables faster transaction processing and more structured customer data management. This study contributes to the field of information systems by providing an integrated E-CRM model tailored for small retail businesses, emphasizing the use of customer interaction features and data-driven service strategies. The findings also imply that the adoption of E-CRM can enhance service effectiveness and support better decision-making in small-scale business environments.   Keywords: E-CRM; Information System; Web-Based System; Customer Service.